2016
DOI: 10.1007/s10853-016-0566-4
|View full text |Cite
|
Sign up to set email alerts
|

The influence of multiscale heterogeneity on recrystallization in nickel processed by accumulative roll bonding

Abstract: Microscopic and sample-scale heterogeneities have been characterized in nickel processed by accumulative roll bonding to a von Mises strain of 4.8, and their influence on recrystallization has been analyzed. The microscopic heterogeneities in this material are mostly associated with regions near the bonding interface, which are more refined and thus possess a higher stored energy than other regions. These regions also contain characteristic particle deformation zones around fragments of the steel wire brush us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(10 citation statements)
references
References 45 publications
(82 reference statements)
3
7
0
Order By: Relevance
“…The presence of these particles (like S1, S2) originated from the fragments of the steel wire brush used during surface preparation. Similar observation was reported in ARB processed Ni alloy [16]. The presence of these steel particles allows the formation of new recrystallized grains with random orientation, which is ascribed to particle stimulated nucleation (PSN) mechanism [31].…”
Section: Microstructural and Textural Characteristics At The Bonded Isupporting
confidence: 79%
See 3 more Smart Citations
“…The presence of these particles (like S1, S2) originated from the fragments of the steel wire brush used during surface preparation. Similar observation was reported in ARB processed Ni alloy [16]. The presence of these steel particles allows the formation of new recrystallized grains with random orientation, which is ascribed to particle stimulated nucleation (PSN) mechanism [31].…”
Section: Microstructural and Textural Characteristics At The Bonded Isupporting
confidence: 79%
“…Results showed that the homogeneity of the texture through the thickness was obtained after 8 ARB cycles (ε = 6.4), but the near surface and near center position was not clearly analyzed [11]. However, the recrystallization behavior along the multiscale heterogeneity of pure Ni was investigated after cold rolling [24] and only for sample processed by ARB to 6 cycles (ε = 4.8) and annealed at 200 °C for different time periods (up to 210 min) [16,17]. It was found that the fraction of {001}〈100〉 Cube texture was lower in the subsurface layers than in the center and intermediate layers of the sample due to the strong shear texture [17].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The universality of the lamellar microstructure formed by GNBs and IDBs [6], and the agreement with respect to Y-junction migration between materials with very different material properties indicates the universality of this recovery mechanism. The strong connection between the characteristics of 1 It should be noted that the kinetics of recrystallization for 3N Ni at 220 °C shown in (c) is slightly different from that reported in a recent recrystallization study of the same deformed Ni [17]. This difference may have its cause in heterogeneities introduced during deformation and therefore a larger experimental error in the estimated activation energy is expected in the 3N Ni compared to that in the 2N Ni.…”
Section: Discussionmentioning
confidence: 64%